Autophagy-induced p62 accumulation is required for curcumol to regulate KLF5-mediated angiogenesis in liver sinusoidal endothelial cells. (30th March 2021) - Gao, Liyuan; Yang, Xiang; Liang, Baoyu; Jia, Yan; Tan, Shanzhong; Chen, Anping; Cao, Peng; Zhang, Zili; Zheng, Shizhong; Sun, Lixia; Zhang, Feng; Shao, Jiangjuan
Graphical abstract: Abstract: Liver pathological angiogenesis is considered to be one of the key events in the development of liver fibrosis. Autophagy is a defense and stress regulation mechanism. However, whether autophagy regulates pathological angiogenesis in liver fibrosis is still questionable. Here, we aimed to study how curcumol regulated liver sinusoidal endothelial cells (LSECs) angiogenesis through autophagy. We found that curcumol (10, 20 and 40 μM) could inhibit the expression of angiogenesis markers in the LSECs. Importantly, we showed that curcumol might influence LSEC pathological angiogenesis by regulating autophagy level. Furthermore, we indicated that the transcription factor Krüppel-like factor 5 (KLF5) was considered as a key target for curcumol to regulate LSEC angiogenesis. Interestingly, we also suggested that autophagy was as a potential mechanism for curcumol to restrain KLF5 expression. Increased autophagy level could impair the suppression effect of curcumol on KLF5. Fascinatingly, our results indicated that curcumol inhibited autophagy and led to p62 accumulation, which might be a regulation mechanism of KLF5 degradation. Finally, in mice liver fibrosis model, we unanimously showed that curcumol (30 mg/kg) inhibited pathological angiogenesis by reducing LSEC autophagy level and suppressing KLF5 expression. Collectively, these results provided a deeper insight into the molecular mechanism of curcumol to inhibit LSEC pathological angiogenesis during liver fibrosis.